Learning Strategy for Islamic Religious Education During the COVID-19 Epidemic - Sunhaji Sunhaji (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Countries all around the world, including Indonesia, are being affected by the COVID-19 epidemic at the moment. As a result of the numerous issues that arose as a direct result of the pandemic, including those that occurred in the field of education, all of the educational pursuits, including teaching and learning, were moved online in order to reduce the risk of the virus spreading further. Learning in Islamic Religious Education encompasses individuals who contend with obstacles, primarily for the purpose of imparting a grasp of the subject matter to students through activities outside of the traditional classroom setting. The purpose of this research is to identify the most effective method for studying Islam in the midst of the COVID-19 pandemic as it exists today. In this investigation, a qualitative strategy is combined with a descriptive research approach. According to the findings, during the COVID-19 epidemic, the most common mode of instruction for Islamic theological and philosophical topics was online study. During the COVID-19 period, the strategies for learning Islamic religious education that were utilized include effective time management, preparation of media and technology, directing and motivating students to study seriously, maintaining discipline, and always maintaining communication with students.